2021
DOI: 10.3390/diagnostics11112030
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, Clinical Presentation and Trends in Indication for Diagnostic Work-Up of Small Intestinal and Pancreatic Neuroendocrine Tumors

Abstract: Background: The incidence of small intestinal (SI) and pancreatic neuroendocrine tumors (siNETs and pNETs) seems to have increased. The increased frequency of incidental findings might be a possible explanation. The study aimed to examine (1) changes in incidence and the stage at diagnosis (2010–2011 vs. 2019–2020), (2) changes in the initial indication for diagnostic workup and 3) the differences in stage between incidentally discovered vs. symptomatic disease during the entire study period. Methods: We perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 27 publications
3
11
0
Order By: Relevance
“…As one hypothesis, the rise in incidence has been attributed to improved and more frequent use of imaging, leading to incidental discoveries of siNET. However, we have previously shown that the proportion of patients incidentally diagnosed in 2010–2011 vs. 2019–2020 was unchanged in our center [ 36 ]. Thus, there may be a genuine increase in siNET incidence together with other contributing factors such as increased awareness among pathologists and clinicians.…”
Section: Discussionmentioning
confidence: 97%
“…As one hypothesis, the rise in incidence has been attributed to improved and more frequent use of imaging, leading to incidental discoveries of siNET. However, we have previously shown that the proportion of patients incidentally diagnosed in 2010–2011 vs. 2019–2020 was unchanged in our center [ 36 ]. Thus, there may be a genuine increase in siNET incidence together with other contributing factors such as increased awareness among pathologists and clinicians.…”
Section: Discussionmentioning
confidence: 97%
“…The majority of pancreatic NENs (pNENs) are well-differentiated non-functioning tumors [ 2 , 3 , 4 ]. During the last 50 years, numerous studies have documented a significant increase in the incidence of pNEN [ 5 , 6 , 7 ]. A possible explanation for this rise includes an increased number of incidentally discovered tumors, greater awareness among pathologists, and a true increase in incidence [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Pancreatic neuroendocrine neoplasms (PanNENs) are rare pancreatic tumors, accounting for 1–2% of all pancreatic tumors [ 1 , 2 , 3 ]. The number of PanNENs cases is steadily increasing [ 4 , 5 , 6 ]. The Surveillance, Epidemiology, and End Results (SEER) database revealed that the annual incidence of patients with PanNENs in the USA were 0.27 per 100,000 in the period 1987–1996, 0.43 in 1997–2006, and 1.01 in 2007–2016 [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…The Surveillance, Epidemiology, and End Results (SEER) database revealed that the annual incidence of patients with PanNENs in the USA were 0.27 per 100,000 in the period 1987–1996, 0.43 in 1997–2006, and 1.01 in 2007–2016 [ 3 ]. The incease is particularly evident in asymptomatic and small non-functioning PanNENs (NF-PanNENs) [ 4 , 5 , 6 ]. According to a population-based study based in the USA, the incidence of pancreatic neuroendocrine tumors (PanNETs) ≤ 2 cm increased by 710% between 1988 and 2012 [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation